2023
DOI: 10.3390/plants12091898
|View full text |Cite
|
Sign up to set email alerts
|

Macro and Micro-Nutrient Accumulation and Partitioning in Soybean Affected by Water and Nitrogen Supply

Abstract: This study aimed to investigate the influence of water availability and nitrogen fertilization on plant growth, nutrient dynamics, and variables related to soybean crop yield. Trials were performed in Teresina, Piauí, Brazil, using randomized blocks in a split-split plot arrangement. The plots corresponded to water regimes (full and deficient), the split plots to N fertilization (0 and 1000 kg ha−1 N-urea), and the split-split plots to harvest times of soybean plants (16, 23, 30, 37, 44, 58, 65, 79 and 86 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…De Aguiar et al [9] identified specific gene members from the L-galactose pathway that could be used in molecular breeding programs to increase the ascorbate content. Setubal et al [10] observed that nitrogen fertilization is inefficient for seed yield in soybeans under drought. Finally, Li et al [11] revised different mechanisms associated with maize salt tolerance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…De Aguiar et al [9] identified specific gene members from the L-galactose pathway that could be used in molecular breeding programs to increase the ascorbate content. Setubal et al [10] observed that nitrogen fertilization is inefficient for seed yield in soybeans under drought. Finally, Li et al [11] revised different mechanisms associated with maize salt tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…The articles published in this SI covered the identification and characterization of transcription factors associated with stress resistance [1][2][3], beneficial endophytic/plant interaction [4,5], and molecular mechanisms involved in crops and fruit plants to stress tolerance [6][7][8][9][10][11].…”
Section: Overview Of Simentioning
confidence: 99%
See 1 more Smart Citation
“…It is due to this symbiotic nitrogen fixation that modern high-protein legume varieties have become one of the most important strategic sources of food supply for humans and animals and an important component of raw industrial materials [5]. Therefore, a considerable increase in the use of legumes and the optimization of the legume-rhizobia symbiosis are of the utmost importance for the construction of stable and sustainable agriculture as well as to obtain high yields.…”
Section: Introductionmentioning
confidence: 99%
“…In modern farming, the nitrogen needs of legume crops are satisfied by the biological fixation of atmospheric nitrogen as well as by the provision of small quantities of mineral nitrogen that act as a top-up due to the large nitrogen export with the crop [4]. Nitrogenase alone is insufficient for modern high-yielding legume types and results in decreased yields [3,5].…”
Section: Introductionmentioning
confidence: 99%